Isolasi dan Karakterisasi Morfologi Cercospora janseana Asal Daun Padi - TondokEfi Toding; Sa’adahRima Nur Halimatu (Jurnal Fitopatologi Indonesia, 2023)
Isolation and Morphological Characterisation of Cercospora janseana Infecting Rice Leaves Narrow brown spot disease in rice plants is among the most destructive diseases. In Indonesia, information about this disease still needs to be improved and needs to get the attention of farmers and researchers. Basic knowledge of the causative pathogen— Cercospora janseana—is needed as a reference in controlling measures and understanding its epidemiology in the future. This study aimed to determine the appropriate isolation techniques for C. janseana and to characterize the morphology of four varieties of rice plants. The isolation techniques used were the method of tissue planting, spore suspension, spore dispersal, and spore attachment. Morphological characterization was carried out by observing the colors and growth of colonies, conidia, and conidiophore, as well as the growth of colonies on different culture media. The results showed that the suitable isolation technique for C. janseana was attaching the spores to water agar and growing them on Martin agar medium. This technique was better than the other three isolation techniques and facilitated the isolation process of C. janseana to obtain pure isolates.